(3Sja GdfWb aj Yde GdefWbs - (3GdBeOj, GdbjGS (B- (3GdTQjaj, eMeO Hf YHO Gddg (B, (3cGf MjG (B1175 (3g`s
(3ChdgG (B:s
(3cja dG fMeO def ejR HaUhd CLfGS GdecGQe fhY GdEfSGf hbO cGf GdWdGH eTJZdjf HbQGAI QSGdI GdCHgQj YfOeG CdaJ dJdc TQMG djHjf ehGba eSGFdgG Yf ebGUOgG hjejR OdGFd eWGdYgG Yf RhGFOgG s
(3BNQgG (B:s
(3hdcfg aQO hdjS HRhL dcfg RhL adjS HaQO dcfg djS HRhO aaQO Ch eQcH ef GdefaUdI GdeGfYI GdLeY eY hVY CMO GdLRFjf hfJjLJg QaY GdLRA GdBNQ afJjLJg GKfJGf ceG fbhd gPG GdLSe EeG TLQ Ch MLQ JeJs
(3JHUQI GdYfhGf (B:s
(3TQM EjSGZhLj ddCHgQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3/431s
(3gOjI GdYGQajf(B1/369s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs